Factors Influencing Healthcare Worker Performance: A Systematic Literature Review Using Thematic Analysis - Tontowi Ashari; Arya Brahmanta; Pipit Festi Wiliyanarti (International Journal of Health and Pharmaceutical (IJHP), 2026)
Background: Healthcare worker performance is a critical determinant of healthcare quality, patient safety, organizational effectiveness, and health system sustainability. Despite extensive research on individual determinants of performance, evidence regarding fragmented analyses remains insufficient and inconclusive. Objective: This systematic literature review aimed to identify factors influencing healthcare worker performance and evaluate their interactions within organizational and professional contexts.Methods: A systematic literature review was conducted following the PRISMA 2020 guidelines. Literature searches were performed across multiple international databases, including Google Scholar, Scopus, Web of Science, Emerald, and Garuda. Eligible studies published between 2020 and 2025 were analyzed using thematic synthesis. Fourteen studies meeting the inclusion criteria were reviewed.Results: Findings indicate that healthcare worker performance is shaped by a combination of psychological, organizational, leadership, and technological factors. Emotional intelligence and spiritual intelligence demonstrated significant positive associations with performance, whereas organizational commitment and job satisfaction frequently acted as mediating variables. Leadership style particularly transformational, digital, and spiritual leadership was associated with improved motivation, adaptability, and organizational effectiveness. Organizational Citizenship Behavior (OCB), effective communication, and digital competence further enhanced healthcare worker performance. Conversely, excessive workload and workplace violence adversely affected employee well-being and productivity. Emerging evidence also highlights the influence of digital transformation and artificial intelligence readiness in modern healthcare settings.Conclusion: Healthcare worker performance is multidimensional and results from interactions among psychological, organizational, and leadership-related factors. Strengthening adaptive leadership, supportive organizational culture, digital readiness, and employee well-being may substantially improve workforce performance and healthcare quality. Further interdisciplinary research is recommended to support evidence-based workforce development in healthcare institutions.